Perencanaan Ulang Tata Letak Fasilitas Menggunakan Metode Activity Relationship Chart (ARC) Pada Taufiq Mart Kabupaten Solok Selatan Sumatera Barat - Diva Nurfitrianti Azizah; Yunus Al Gaza; Riza Muharmayenti; Zulhan Andika (CV. KAMPUS AKADEMIK PUBLISHING, 2024)
Taufiq Mart is a supermarket that offers various types of goods including household necessities, stationery, frozen food and fruit. Even though it is popular among consumers, Taufiq Mart has problems with less than optimal store layout, such as there are still many empty rooms so it needs to reorganize the Taufiq Mart facilities which are not yet optimal. To overcome this problem, it is necessary to redesign the store layout using analytical methods such as the Activity Relationship Chart (ARC), with data from various sources. The analysis results show that the freezer section is the main priority in remaking the layout because it has the highest TCR value. It is hoped that the new layout changes will increase operational efficiency and consumer comfort at Taufiq Mart.